E-059 The prognostic significance of age in the adolescent and young adult population with stroke status post mechanical thrombectomy. (23rd July 2022) - Lu, V; Silva, M; Burks, J; Luther, E; Abdelsalam, A; Starke, R; Collaborators, S
Abstract : Background: Younger age has been shown to predict better functional outcomes status post mechanical thrombectomy (MT) in the setting of stroke. The significance of this in the adolescent and young adult (AYA) population however is not defined. Correspondingly the goal of this study was to determine the prognostic significance of age in this specific demographic following MT. Methods: A prospectively maintained international multi-institutional database STAR (Stroke Thrombectomy and Aneurysm Registry) was reviewed for all patients aged between 12–18 years old (adolescent) and 19–25 years old (young adult). Parameters were compared using chi-squared and t-test analyses, and associations were interrogated using regression analyses. Results: A total of 41 patients with a mean age of 19.7 ± 3.3 years satisfied all criteria with 16 (39%) adolescents and 25 (61%) young adults. There were more males than females (59% vs 41%), with a majority of White patients (67%) and mean Modified Rankin Scale (MRS) score of 0.1 ± 0.4 prior to stroke. Strokes were most common in the anterior circulation (88%), with the middle cerebral artery distribution the most common vessel (59%). Mean times to groin and then to reperfusion were 327 ± 229 minutes and 52 ± 42 minutes with an average number of 2.2 ± 1.2 attempts needed. There were only 3 (7%) cases of re-occlusion. Mean MRS score at last follow-up was 1.8 ± 1.5. Between adolescent and young adult subgroups, mean MRS score at last follow-up was statistically lower in the adolescent versus young adult subgroup (1.1 ± 1.4 vs 2.2 ± 1.4, P=0.03). Regression analysis indicated significant independent association between age and last follow-up MRS score within the AYA demographic (OR 1.43, P=0.02). Conclusion: MT for stroke treatment in the AYA demographic is both safe and effective. Even within this relatively young demographic, age remains significantly associated with functional outcome. The implication that stroke outcomes status post MT is dependent on age in those between 12–25 years needs greater validation in order to develop effective age-specific protocols for long-term care. Disclosures: V. Lu: None. M. Silva: None. J. Burks: None. E. Luther: None. A. Abdelsalam: None. R. Starke: None. S. Collaborators: None.